Simulation of suspended cable-driven parallel robot on SimulationX. (10th April 2023) - Jomartov, Assylbek; Tuleshov, Amandyk; Kamal, Aziz; Abduraimov, Azizbek
Currently, research is being carried out on a new type of parallel robots, such as cable-driven parallel robot. The cable-driven parallel robot are parallel robots with flexible (cables), with a large workspace, with high speeds and accelerations of the end effector. In the cable-driven parallel robot, cables can only work in tension, and cable-driven parallel robot lose their performance when they are compressed. This feature severely limits the development and application of cable-driven parallel robots and requires further development of cable-driven parallel robot modeling on various software systems. Currently, Adams multibody dynamics software is widely used to create and test virtual prototypes of mechanical systems. But for cable-driven parallel robot modeling, the Adams program is quite complex and expensive to use. In this article, the simulation of the cable-driven parallel robot is carried out on the SimulationX software. Unlike other software packages, SimulationX is more accessible and cheaper and is well suited for cable-driven parallel robot simulation. Cable-driven parallel robot modeling on SimulationX allows you to identify the main design flaws even before its prototype is made. A model on the SimulationX software of a suspended cable-driven parallel robot with a point mass end effector, taking into account the elastic-dissipative properties of cables, was developed. The prototype of suspended cable-driven parallel robot with a point mass end effector was manufactured. Experimental researches of the prototype of the suspended cable-driven parallel robot with a point mass end effector confirmed the correctness of the application of the model on SimulationX for practical calculations.